Jagati of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
A view of the Jagati (raised plinth), interspersed with niches, serves as the foundational base upon which the Chaunsath Yogini Temple stands. Most niches of this plinth are empty, unlike a few which contain loose images of goddesses. On the edge of this plinth are the remains of the kakshasana (dwarf walls with seat backs). Most niches of this plinth are empty, unlike a few which contain loose images of goddesses. On the edge of this plinth are the remains of the kakshasana (dwarf walls with seat backs).